2018
DOI: 10.31436/ijcs.v1i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Attitude of First Aid Among Health Sciences University Students

Abstract: Objective: As the incidence of emergencies has steadily increased in recent years, it is important to en-sure that individuals, including university students, are adequately trained to deal with such events. This study aimed to assess the level of knowledge and awareness of, and attitudes towards, first aid among IIUM Kuantan campus students. Method: A quantitative cross-sectional survey with stratified random sam-pling study was conducted among 348 students at the International Islamic University Malaysia (II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
(7 reference statements)
1
7
1
Order By: Relevance
“…In this study, researchers found that majority of the respondents had moderate knowledge of first aid. This finding was similar to a study done in a public university in Malaysia as the researchers concluded that majority of the respondents had intermediate knowledge of first aid among the respondents (Jamaludin, Allif Bin Zakaria, Saidi, & Chan, 2018). Both findings may be due to the respondents who were students from health science and science-based related to the healthcare sector.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, researchers found that majority of the respondents had moderate knowledge of first aid. This finding was similar to a study done in a public university in Malaysia as the researchers concluded that majority of the respondents had intermediate knowledge of first aid among the respondents (Jamaludin, Allif Bin Zakaria, Saidi, & Chan, 2018). Both findings may be due to the respondents who were students from health science and science-based related to the healthcare sector.…”
Section: Discussionsupporting
confidence: 88%
“…The finding of this study is in line with previous studies conducted in the United Arab Emirates (54.2%), 12 India (53.3%), 13 and Kuwait (49.0%). 14 The finding of this study was higher than a study conducted in Pakistan (40.3%), 15 Malaysia (42.8%), 16 and Maharashtra (41.3%). 17 The possible justification for this variation might be due to differences in the study period, sample size, and socio-demographic characteristics of the respondents.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, males were found to have better first aid knowledge than females. Nevertheless, previous studies found that females were having better knowledge of burn first aid among members of sporting and recreation clubs 12 ; better first aid knowledge among university students in Jordan 16 and health sciences university students in Malaysia 17 . The difference of results might be due to the differences in designs of study and statistical analyses, as this study targeted all citizens at Hong Kong and used multiple regression.…”
Section: Discussionmentioning
confidence: 89%
“…This finding was consistent with previous studies from both Hong Kong and overseas. [7][8][9][10][11][12][13][14][15][16][17] The number of years past after the completion of last first aid training was found to be significantly associated with a lower first aid knowledge. This finding was like another study on burn first aid that, among those had attended a first aid course, the knowledge was better if the course was undertaken within the previous five years.…”
Section: Discussionmentioning
confidence: 99%